(untitled) (International Association of Biologicals and Computational Digest, 2022)
CH4 is a powerful greenhouse gas. It is present in the atmosphere in very low concentrations. Nevertheless, it is the third most important greenhouse gas after water vapour and carbon dioxide (CO2). Water vapour is present in variable amounts. CO2 contributes about 50% to the enhanced greenhouse effect, CH4 about 15-20% and nitrous oxide (N2O) about 6%. Methane (CH4) is a hydrocarbon and the primary component of natural gas. Methane is also a potent and abundant greenhouse gas (GHG), which makes it a significant contributor to climate change, especially in the near term (i.e., 10–15 years). Methane is emitted during the production and transport of coal, natural gas, and oil. Emissions also result from livestock and other agricultural practices and from the decay of organic waste in municipal solid waste landfills and certain wastewater treatment systems. Methane is the second most abundant GHG after carbon dioxide (CO2), accounting for 14 percent of global emissions. Though methane is emitted into the atmosphere in smaller quantities than CO2, its global warming potential (i.e., the ability of the gas to trap heat in the atmosphere) is 25 times greater. As a result, methane emissions currently contribute more than one-third of today’s anthropogenic warming In this study an integrated assessment is performed of the contribution of methane to climate change especially from agricultural fields and the options for methane control. The main aim of the study was to analyze future trends in global methane emissions, the associated climate change, and the costs of emission control in terms of agricultural surface methane emissions.